Online Attendance System for Village Officials: A Case Study on the Application of Android Technology - Syaiful, Syaiful; Astutik, Widya; Fitriana, Novira; Laila Fatika Agustini, Ayu Febriana (Universitas Nurul Jadid, 2025)
The attendance tracking process for village officials in Sogaan Village has traditionally been conducted manually, leading to issues such as data inaccuracies, delayed reporting, and time wastage. This study aims to design and implement an Android-based Online Attendance System for Sogaan Village officials to address these problems. The research methodology consists of three main stages. First, a needs analysis was conducted through interviews and observations with village officials to identify required features. Second, system design was carried out, including user interface development, attendance feature configuration, and integration with a database for attendance data management. Third, the application was implemented using Android technology, involving system testing to ensure functionality and reliability. The goal of this research is to enhance the efficiency and accuracy of the attendance process for village officials. By utilizing an Android-based application, the system is expected to facilitate real-time attendance tracking, reduce manual errors, and simplify reporting and monitoring. Additionally, the system aims to improve transparency and accountability in attendance administration for village officials.